Answer:
what is the answer?
Step-by-step explanation:
10 x squared minus 4 y + 2 x squared minus y
9x^2-2y+3x^2-3y
Collect like terms
9x^2+3x^2-2y-3y
=12x^2-5y
10x^2-4y+2x^2-y
10x^2+2x^2-4y-y
9x^2-2y+3x^2-3y is equivalent to
Check all the options
6 x squared minus y + 6 x squared minus 5 y
6x^2-y+6x2-5y
12x^2-6y
6 x squared minus y + 3 x squared minus 4 y
6x^2-y+3x^2-4y
9x^2-5y
12x^2-5y
11 x squared + 2 y + x squared minus 3 y
11x^2+2y+x^2-3y
12x^2-y
Lateral Area = Area of 2 triangle + Area of slant rectangle + area of back rectangle
Lateral Area = (5m)(3m) + (6m) (36m) + (3m) (36m)
LA = 15m² + 216m² + 108m²
LA = 339 m²
SA = (5m)(3m) + (6m) (36m) + (3m) (36m) + (5m)(36m)
SA = 15m² + 216m² + 108m² + 180 m²
SA = 519 m²
x = 36
Answer:n
n